Cytochrome b5 and Cytokeratin 17 Are Biomarkers in Bronchoalveolar Fluid Signifying Onset of Acute Lung Injury - Ménoret, Antoine; Kumar, Sanjeev; Vella, Anthony T. (PLOS ONE, 2012)
Acute lung injury (ALI) is characterized by pulmonary edema and acute inflammation leading to pulmonary dysfunction and potentially death. Early medical intervention may ameliorate the severity of ALI, but unfortunately, there are no reliable biomarkers for early diagnosis. We screened for biomarkers in a mouse model of ALI. In this model, inhalation of S. aureus enterotoxin A causes increased capillary permeability, cell damage, and increase protein and cytokine concentration in the lungs. We set out to find predictive biomarkers of ALI in bronchoalveolar lavage (BAL) fluid before the onset of clinical manifestations. A cutting edge proteomic approach was used to compare BAL fluid harvested 16 h post S. aureus enterotoxin A inhalation versus BAL fluid from vehicle alone treated mice. The proteomic PF 2D platform permitted comparative analysis of proteomic maps and mass spectrometry identified cytochrome b5 and cytokeratin 17 in BAL fluid of mice challenged with S. aureus enterotoxin A. Validation of cytochrome b5 showed tropic expression in epithelial cells of the bronchioles. Importantly, S. aureus enterotoxin A inhalation significantly decreased cytochrome b5 during the onset of lung injury. Validation of cytokeratin 17 showed ubiquitous expression in lung tissue and increased presence in BAL fluid after S. aureus enterotoxin A inhalation. Therefore, these new biomarkers may be predictive of ALI onset in patients and could provide insight regarding the basis of lung injury and inflammation.